Resiliency of business strategies to disasters the case of MSMEs in Tacloban City, Philippines - Acidre, Althea Marie Aragoncillo; Cirera, Careloid Jane Villasin; Egargo, Fleur Jasha Duran
Several studies have been undertaken on Micro, Small, and Medium-sized Enterprises' (MSMEs) Disaster Risk Management when affected by disasters. However, very few studies have focused on the robustness of MSMEs' strategies in catastrophic disasters, such as typhoons, pandemics, and others. This study attempts to explore resilience indicators of business strategies of MSMEs and identify the characteristics that enable them to operate a resilient and sustainable business during and after disasters. Using an exploratory multiple case study design, the researchers conducted a semi-structured interview with 12 purposively selected MSME owners or managers in Tacloban City. The data collected from the interview were analyzed using a thematic analysis which revealed disaster impacts on MSMEs and factors that influence the resilience of MSMEs vital to business sustainability. Findings interpreted showed that, despite being more reactive than proactive in the face of disasters, entrepreneurial characteristics have shaped MSMEs' resilience to disasters. The integration of their strategies, such as expanding customer base and product offerings, diversification, product/service development, and sustaining an integrated relationship with customers and suppliers, as well as their response through crisis adaptation and disaster recovery, has also revealed the resiliency of their business strategies. This demonstrates that the resiliency of an MSME is grounded in its leadership and strategy, resources and relationships, and preparedness and managing risks. Therefore, MSME owners and managers, together with government agencies, must consider these indicators in devising disaster post-recovery strategies and policies toward sustainability and profitability.